# 1 + 2log 3 - log x = log(x+1)What is x?

### 1 Answer | Add Yours

First, we'll impose the constraints of existence of logarithms:

x>0

and

x+1>0

x>-1

The common interval of admissible values for x is (0 , +inf.).

We'll re-write the term 2log 3 using the power rule of logarithms:

2log 3 = log 3^2

2log 3 = log 9

We'll re-write the equation, moving all terms that contain the variable x to one side:

1 + log 9 = log(x+1) + log x

Now, we'll solve the equation, applying th product rule of the logarithms:

log9 + log 10 = lg(x+1) + lgx

log 9*10 = log[x*(x+1)]

Because the bases of logarithms are matching, we'll use the one to one property:

x*(x+1)=9*10

We'll remove the brackets and we'll move all terms to one side:

x^2 +x -90=0

We'll apply the quadratic formula:

x1=[-1+ sqrt(1+4*90)]/2=(-1+19)/2=9 > 0

x2=(-1-19)/2=-10 < 0

**We'll reject the second solution and the equation will have just the solution x = 9.**